Effect of Extracts from Zygophyllum Fabago on Growth and Activity of Candida Albicans and Aspergillus Flavus - Ali, B. Z.; AL- Qaisi, E. E. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The study  was conducted to evaluate  the anti fungal activity ofwater and alcohol ic  extracts (cold and  hot) and the crude alkaloidextracts  of  leaves, seeds  and  roots  of  Zygophyllum  fabago  plant against a standard isolate of C. albicans and an isolate of A. jlavus which was proved to produce aflatoxins. Investigation of presence of active antimicrobial compounds in this plant parts was carried out, crude al kaloid extract was also separated using TLC technique. The antifungal activity of all these extracts was estimated against the two fungi.  Results showed  variation  in  anti fungal activity  of  different extracts  against  C. albicans, where  the MIC  values of  the  water extracts (cold and hot) and the alcoholic extracts (cold and hot) from leaves   was  (50)   mg/ml,   (50,40,30,20)   mg!ml                         from  seeds   and (50, 40, 60,60) mg/ml from root, respectively, Whereas the MIC of the crude alkaloid extracts from leaves, seeds and roots were (40,50,50) mg/ml respectively which indicate a higher antifungal activity of the crude alkaloid extract from leaves followed by the same extract from roots  then   seeds.   Additionally,   crude  alkaloid   extracts   showed complete                 inhibition      of                   spores           germination  of                    A.   jlavus             at concentrations (60,70,80)mg/m l,  whereas other lower concentrations delayed spores germination. Various concentrations of seeds alkaloid extracts also inhibit surface growth of A. jlavus colonies at (60,70) mg/ml. Bioautography of seeds alkaloid extracts using TLC technique revealed  the  presence  of   here  compounds  in  the  extract,  these compounds showed a different inhibitory activity on the growth of A. jlavus.